Теоретичне забезпечення діагностики як превентивний захід запобігання банкрутства підприємства - Соколова, Л. В.; Полозова, Т. В. (НТУ "ХПІ", 2014)
У статті розглянуто поняття діагностики, визначено напрями та завдання економічної діагностики. Здійснено поглиблений аналіз літературних джерел в області концептуальних підходів до діагностики (дослідницька, фінансово-аналітична, управлінська, інформаційна, антикризова, консультаційна). Запропоновано авторський підхід до діагностики банкрутства підприємства. Визначено мету і функції діагностики банкрутства підприємства. Виділено рівні впровадження превентивних заходів запобігання банкрутства підприємства.

The notions of the diagnostics, directions and problems of the economic diagnostics are considered. The detailed analysis of the literary sources in the field of conceptual approach to diagnostics (exploratory, financialanalytical, management, information, uncrisis, consultation) is realized. The categories "financial diagnostics" and "uncrisis diagnostics" are considered. The author's approach to diagnostics bankruptcy enterprises is offered. The functions and primary tasks of the diagnostics bankruptcy enterprises are determined. The level of the preventive action on prevention bankruptcy enterprises (operative and strategic) are offered. The results of the diagnostic research are one of most generalized facilities of the reception to reliable information on condition and deflection in development of the investigation enterprise. The prospects of the further research are determined. The prospect of the further research is an analysis methdological approach to undertaking the diagnostics bankruptcy enterprises.
Theoretical ensuring the diagnostics as preventive action on prevention bankruptcy enterprises
Keywords: завдання; економічна діагностика; інфляційні коливання; криза неплатежів; diagnostics; problems; economic diagnostics; diagnostics bankruptcy enterprises; preventive actions on preventions bankruptcy